Contribution to the description. record and onomatology of Aceria oleae (Nalepa, 1900) (Acari: Eriophyidae) - Hatzinikolis, E.N. (ENTOMOLOGIA HELLENICA, 1986)
The female of Aceria oleae is described and illustrated and for first time, the dimensions of the different parts and accessories of the body are given. The male of this mite is also described and illustrated for first time. The world distribution as well as the local distribution in Greece are recorded. Information on the onomatology is provided.